Characterizing mathematical discourse according to teacher and student interactions: The core of mathematical discourse - Sedef Çelik Demirci; Adnan Baki (Journal of Pedagogical Research, 2023)
The discussion on the development of mathematical discourse plays a key role in the determination of the in-classroom interactions in mathematics learning and instruction. The present study aims to present a theoretical framework for the nature of mathematical discourse that addresses the teacher and student interaction in the classroom. Previous studies attempted to discuss the theoretical structure in mathematical discourse with the embedded theory approach. The findings revealed the core of mathematical discourse that reflected the structure of mathematical discourse based on open, axial and selective codes determined based on the embedded theory approach. The external structure of this core reflects the types of in-classroom interaction, while the internal structure reflects the development of the mathematical discourse. The external structure included four types of interaction: teacher, teacher-class, teacher-student, and student-student. The internal structure includes mathematical discourse movements associated with three stages: motivation, explanation of mathematical ideas, and achievement of mathematical ideas. The external structure of mathematical discourse core revealed the general state of in-classroom interaction core, and the internal structure revealed the specific mathematical discourse based on the mathematical content. It could be suggested that the discourse movements in the mathematical discourse core determined in the present study would provide guidelines for mathematical communications. The study also includes recommendations for future studies on the employment of this general and specific theoretical mathematical discourse framework.